2004
DOI: 10.1093/sleep/27.6.1163
|View full text |Cite
|
Sign up to set email alerts
|

Who Reports Insomnia? Relationships with Age, Sex, Ethnicity, and Socioeconomic Deprivation

Abstract: Socioeconomic factors and ethnicity are significant independent predictors of reported insomnia symptoms. This finding has important implications for the provision of treatment services to those most in need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
5
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 0 publications
5
72
5
1
Order By: Relevance
“…Our research supports other studies that have found poorer sleep quality among those with low educational qualifications (Kietjna et al, 2003;Moore et al, 2002;Rocha et al, 2002;Stewart et al, 2006), who are not working (Paine et al, 2004;Rocha et al, 2002), and with low income (Lauderdale et al, 2006;Friedman, Love, Rosenkranz, Urry, Davidson, Singer et al, 2007). However, our study goes beyond existing research in two ways.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our research supports other studies that have found poorer sleep quality among those with low educational qualifications (Kietjna et al, 2003;Moore et al, 2002;Rocha et al, 2002;Stewart et al, 2006), who are not working (Paine et al, 2004;Rocha et al, 2002), and with low income (Lauderdale et al, 2006;Friedman, Love, Rosenkranz, Urry, Davidson, Singer et al, 2007). However, our study goes beyond existing research in two ways.…”
Section: Discussionsupporting
confidence: 89%
“…in flats with insubstantial walls may result in night-time disturbance through noise from neighbours, which is unlikely in more salubrious areas of detached housing. Low SES is also associated with living in disadvantaged neighbourhoods (Paine et al, 2004) and areas with greater problems of noise, crime, anti-social behaviour, safety and security, which may directly compromise sleep quality. …”
Section: Explaining the Ses Gradient In Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Os principais estudos, neste contexto, foram realizados com crianças e adolescentes norte-americanos com diferentes origens étnicas, normalmente, comparando origens africanas e europeias e têm verificado uma tendência de jovens com menor nível socioeconômico apresentarem pior qualidade de sono, maiores prevalências de insônia, menor duração do sono, maior frequência de despertares noturnos e apneia [4][5][6][7][8][9][10][11] .…”
Section: Artigo Original Introduçãounclassified
“…These include demographic and personal characteristics (e.g. being female [12], older age [13][14][15][16], lower education/socioeconomic status [17][18][19], being divorced/single [20], obesity [21,22]), unhealthy behaviors (e.g. low physical activity [15,23,24], alcohol intake [25,26], smoking [27][28][29][30][31]), poor physical health [32,33] and physical symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%